PENGARUH KOMBINASI GYPSUM DAN FLY ASH TIPE C PADA KUAT TEKAN MORTAR - Aulia Rahman (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2022)
The use of gypsum and fly ash is very common in construction of Indonesia. Both of these materials are used because of Indonesia's rich natural potential. Gypsum was chosen because it has the same chemical composition as cement, which is calcium (Ca), while type C fly ash also shows the same content. By combining the two materials, the researchers tried to study their impact on the compressive strength of mortar. The proportion of cement was reduced from 100%, 50%, 25%, and 0%, while the rest was replaced by a combination of gypsum and type C fly ash. Then, the samples were tested at the age of 7 and 14 days to see the compressive strength performance on early days of hardening. Samples with no substituent composition showed the highest compressive strength of 23.3 MPa, then it continued to decrease as the cement mixture became less, until the lowest was 7 MPa in samples composed only of gypsum and fly ash. There was a significant increase in performance of sample 4 which only contained 25% cement, but it was indicated that the cause was not due to composition, but other factors such as water ratio and compaction. Keywords: gypsum, type C fly ash, mortar.